An Overview of Cerebral Palsy in Children - Adhikari, Tulashi (Journal of Nursing Education of Nepal, 2023)
Cerebral palsy is one of the leading disorders of neurological impairment in childhood, caused by damage to the developing brain from congenital malformation, injuries and anoxia at any time during fetal life, birth and early year of child’s life. Most of the affected children will develop symptoms in infancy or early childhood with motor impairments such as spasticity, muscle weakness and ataxia. As a result, this disorder influences not only the child’s everyday functioning but also the activities of the whole family. However, proper and early management of this disorder can improve the quality of life of the child to a great extent. Health professionals including nurses can use this information in early identification, prevention and management through rehabilitation services to the child, parent and family member. The aim of this review is to highlight cerebral palsy in childhood and several evidence was reviewed from different sources.